ANALYSIS OF THE EFFECT OF BRAND EXPERIENCE ON BRAND LOYALTY THROUGH BRAND SATISFACTION AND BRAND TRUST IN WAKOEL REMPAH RESTAURANT SURABAYA - khu, steven; Sukesi, Sukesi (Universitas Dr. Soetomo, 2020)
The existence of a brand is considered a business pillar so that it can attract consumers to use the product. The purpose of this study was to analyze brand experience on brand loyalty through brand satisfaction and brand trust in customers of Wakoel Rempah Restaurant, Surabaya.The approach used in this research is a quantitative approach. This type of research is explanatory research. The population and sample used in this study were 125 respondents of Wakoel Rempah Restaurant Surabaya.The analysis technique used in this research is SEM PLS.The results of the analysis in this study prove that Brand Experience has a significant effect on Brand Satisfaction and Brand Trust but not significantly on Brand Loyalty. The analysis also shows that Brand Satisfaction has a significant influence on Brand Loyalty and Brand Trust. Furthermore, Brand Trust has a significant effect on Brand Loyalty. Likewise, it is also proven that Brand Experience has a significant influence on Brand Loyalty through Brand Satisfaction but Brand Experience does not have a significant effect on Brand Loyalty through Brand Trust.